Economics of Scale Versus Technological Change: An Aggregate Product Function for Switzerland - Mountain, Dean C. (The Review of Economics and Statistics, 1986)
In estimating a production function for an economy, constant returns to scale has been a traditionally maintained hypothesis. In modelling Switzerland's gross output as a function of labor, capital and imports, a general functional form is selected which displays increasing returns to scale and is not Hicks-neutral. It is a technology which is labor saving, import saving and capital using. This paper also quantifies the mismeasurements associated with using a constant returns to scale model to estimate such variables as own-elasticities of demand, elasticities of substitution, impacts on factor income and rate of technical progress.